The cross-cutting contribution of the end of neglected tropical diseases to the sustainable development goals - Mathieu Bangert; David H. Molyneux; Steve W. Lindsay; Christopher Fitzpatrick; Dirk Engels (BMC, 2017)
Abstract The Sustainable Development Goals (SDGs) call for an integrated response, the kind that has defined Neglected Tropical Diseases (NTDs) efforts in the past decade. NTD interventions have the greatest relevance for SDG3, the health goal, where the focus on equity, and its commitment to reaching people in need of health services, wherever they may live and whatever their circumstances, is fundamentally aligned with the target of Universal Health Coverage. NTD interventions, however, also affect and are affected by many of the other development areas covered under the 2030 Agenda. Strategies such as mass drug administration or the programmatic integration of NTD and WASH activities (SDG6) are driven by effective global partnerships (SDG17). Intervention against the NTDs can also have an impact on poverty (SDG1) and hunger (SDG2), can improve education (SDG4), work and economic growth (SDG8), thereby reducing inequalities (SDG10). The community-led distribution of donated medicines to more than 1 billion people reinforces women's empowerment (SDG5), logistics infrastructure (SDG9) and non-discrimination against disability (SDG16). Interventions to curb mosquito-borne NTDs contribute to the goals of urban sustainability (SDG11) and resilience to climate change (SDG13), while the safe use of insecticides supports the goal of sustainable ecosystems (SDG15). Although indirectly, interventions to control water- and animal-related NTDs can facilitate the goals of small-scale fishing (SDG14) and sustainable hydroelectricity and biofuels (SDG7). NTDs proliferate in less developed areas in countries across the income spectrum, areas where large numbers of people have little or no access to adequate health care, clean water, sanitation, housing, education, transport and information. This scoping review assesses how in this context, ending the epidemic of the NTDs can impact and improve our prospects of attaining the SDGs.